2003
DOI: 10.1007/s00384-003-0543-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function and continence after ileo pouch anal anastomosis: a comparison between a meta-analysis and a questionnaire survey

Abstract: This study underlines that the operation itself, freeing patients of their disease, provides the major satisfaction and improvement of quality of life, even when patients have pouch-related complications such as sexual dysfunction and some degree of fecal incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
2
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 10 publications
4
43
2
5
Order By: Relevance
“…Sexual dysfunction affects fertility adversely. 33 Dozois et al and Hueting et al 27,28 have suggested that women are at the most risk. Although these studies measured sexual function using nonstandardized techniques, our results, using validated instruments, indicate that women do indeed experience abnormal function postoperatively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Sexual dysfunction affects fertility adversely. 33 Dozois et al and Hueting et al 27,28 have suggested that women are at the most risk. Although these studies measured sexual function using nonstandardized techniques, our results, using validated instruments, indicate that women do indeed experience abnormal function postoperatively.…”
Section: Discussionmentioning
confidence: 96%
“…Dozois et al 27 described the negative impact on female sexual function caused by pelvic dissection during open IPAA. More recently, Hueting et al 28 found sexual function abnormalities after open IPAA.…”
mentioning
confidence: 97%
“…5,12,13 However, these studies did not use validated instruments to assess sexual function. Gorgun et al 14 used the IIEF to assess sexual function in 122 patients who had IPAA and found an improvement overall after IPAA but preoperative sexual function was not assessed prospectively, rather that patients were asked to recall their preoperative sexual function often many years after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, after RPC patients generally have increased bowel frequency, decreased stool consistency, and potentially daytime and nighttime incontinence. [3][4][5] The reported overall postoperative complication rate is 29 to 63 percent. 3,6 One of the most feared complications after RPC is sepsis caused by failure of a pouch or anastomotic suture or staple line.…”
mentioning
confidence: 98%